UNVEILING CARBON TRANSPARENCY: THE IMPACT OF ENVIRONMENTAL MANAGEMENT AND MEDIA EXPOSURE WITH FIRM SIZE AS A MODERATOR - Arinta, Yusvita Nena; Yudiana, Fetria Eka; Waluyo, Agus; Bahjatullah, Qimangku; Saifudin, Saifudin; Azahra, Prizka Dini; Lestari, Indah (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study aims to examine the effect of the Environmental Management System (EMS) and Media Exposure on Carbon Emission Disclosure with Company Size as a moderating variable. The research is motivated by the growing global concern over environmental issues, particularly carbon emissions, which have become an essential indicator of corporate sustainability. EMS implementation and media pressure are considered potential drivers of transparency in carbon emission disclosure, while company size is expected to strengthen these relationships. This research employs a quantitative approach using secondary data obtained from annual and sustainability reports of companies listed on the Indonesia Stock Exchange. Data analysis was conducted through Moderated Regression Analysis (MRA) using SmartPLS. The findings reveal that EMS has a positive but insignificant effect on Carbon Emission Disclosure. In contrast, Media Exposure has a positive and significant effect on Carbon Emission Disclosure. Furthermore, Company Size does not moderate the relationship between EMS and Carbon Emission Disclosure, nor between Media Exposure and Carbon Emission Disclosure. Theoretically, this study contributes to the environmental accounting literature by emphasizing the pivotal role of media in encouraging transparency of carbon emission disclosure, while EMS and company size have not shown consistent impacts. Practically, the findings suggest that companies should pay closer attention to media exposure as an effective external pressure to enhance environmental accountability. Additionally, regulators may use these insights as a basis for strengthening carbon disclosure policies in Indonesia.